Relationship between Physiological Resorption of Primary Molars with Its Permanent Successors, Dental Age and Chronological Age - Antonia M. Caleya; Nuria E. Gallardo; Gonzalo Feijoo; M. Rosa Mourelle-Martínez; Andrea Martín-Vacas; Myriam Maroto (MDPI AG, 2022)
The aim of the present study was to analyse root resorption of the primary mandibular molars and their relationship with their permanent successors and the age of the patient. Methods: The sample consisted of 408 digital panoramic radiographs. The mesial and distal crown-to-root ratios (CRR) of #74 and #75 were calculated by dividing the measures of the length of each root by its coronal height. The Demirjian formation stage of the premolar was established, and dental age was determined. A descriptive and statistical analysis was performed using SPSS to determine the correlation between the variables (Pearson's correlation coefficient) and to identify the differences between them (Student's t-test), with a confidence level of 95%. Results: 723 molars were measured, and tables of CRR depending on dental and chronological age were obtained. The CRR decreased with increasing dental and chronological age, but not uniformly. The CRR of #74 and #75 decreased slightly when the successor premolar was in the initial stages of formation. Gender differences were obtained with respect to chronological age, mainly in girls, because the root resorption of #74 was always more advanced, and the formation of the #34 more advanced. Conclusions: Root resorption of the molar is slight and progressive when the successor premolar begins formation until stage D, and becomes higher starting at stage E. It is possible to determine the state of the child's maturation and the CRR according to dental and chronological age.